PERSEPSI MASYARAKAT TERHADAP PERBANKAN SYARIAH DI KABUPATEN PASAMAN BARAT - Yuliana .. (UIN Imam Bonjol Padang, 2020)
The formulation of the problem of this research is how the public's perception of Islamic banking. The purpose of this study is to seek academic answers to how the public's perceptionof Islamic banking. This research is a descriptive field research which aims to describe the reality in the field with a qualitative approach. The qualitative approach is an effort to improve data collection. This community perception is motivated by their lack of knowledge of Islamic banking operations, whether bank interest is prohibited or not. Furthermore, thesedifferences in perceptions are also influenced by the services of the Islamic bank itself, and which are also influenced by Islamic banking operations. not in accordance with the Islamic concept. Regarding the factors that influence public perceptions of Islamic banking, it can be concluded that the knowledge factor and the acceptance factor, the service economy factor, ngan and location and idealism or religion.Keywords: Public Perception, and Islamic Banking.